Assessment of the pre- and post-workout dietary profile of Crossfit® practitioners - Brustolin, Mario Rodrigo; Souza, Carolina Tarcinalli; Souza, Debora Tarcinalli; Ferron, Artur Junio Togneri [UNESP]; Francisqueti-Ferron, Fabiane Valentini (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2024)
CrossFit (R) is a modality of high intensity exercise that requires the consumption of specific and adequate nutrients guaranteeing a better performance and avoiding injuries, acidosis and the risk of hypoglycemia. Thus, the objective of the research was to evaluate the pre and post training dietary profile of CrossFit (R) practitioners. Being a cross-sectional study carried out during the months of August and October 2020 in the CrossFit (R) box C. Miles Training in the city of Bauru-SP. They were evaluated as anthropometric measures and a nutritional anamnesis was performed. Twenty people participated in the study, 11 men and 9 women. It was noted that the average BMI was 25.2 kg / m2 in women and 26.0 kg / m2 in men. Regarding the participants' pre -training, 15 of them eat 30 minutes before training, and in the post -training, 14 of them have a habit of eating 1 hour after training, especially with dinner. It is concluded that CrossFit (R) practitioners have habits of eating in the pre and post training. It is worth mentioning that for a better performance and results of the training, the ones necessarily have to follow a balanced diet according to the activity performed and the bioavailability of each one.
Keywords: CrossFit (R); Feed profile; High intensity training; Diets; Eating behavior